Hydatid fluid form Echinococcus granulosus is recognized by Clec9A in BMDCs, induces autophagy and polarizes the T cell response towards Th1/Th17 profiles in vitro - Chop, Maia (2022)
Background: Cystic echinococcosis is caused by Echinococcus granulosus. This parasite develops cysts in the host that are filled with hydatid fluid (HF). Autophagy plays a key role in antigen presentation promoting activation of T cells. The aim of this work is to analyze if HF could polarize the T cell response in vitro. Methods: HF was collected from infected cattle. Expression of Clec9a was evaluated by FACS in FLT3L-BMDCs. Autophagy induction was evaluated by FACS, qPCR, confocal and TEM. Rapamycin (20 nM) and chloroquine (100μM) were used to analyze autophagic flux. T cell cytokine profiles were analyzed by qPCR. Results: HF induces a downmodulation of Clec9a in BMDCs (n=3 **p<0.01). Enhanced number of autophagosomes were observed by TEM in HF-stimulated BMDCs compared to control cells. Also, HF-stimulated BMDCs significantly enhanced the MFI of LC3+ structures in comparison with unstimulated cells (**p<0.01). The autophagic flux was analyzed by measuring LC3II attached to autophagosome membranes by FACS. HF induced an increased in the percentage of LC3+ cells compared to untreated cells (30.2% vs 23.1%) and this phenomenon was enhanced by the inhibition of lysosomal acidification (28.4% vs 40.6%). Then, we evaluated the expression of beclin-1, lc3, tfeb and atg16l-1 genes. We observed that HF induces a significant increase in the transcriptional expression of lc3 and beclin-1 (n=3, **p <0.01 vs control). Finally, we measured the expression of il-4, il-5, il-6, il-10, il-12, il-13, il-17, tnf-, tgf- and inf-in splenocytes by qPCR, finding that HF-stimulated BMDCs increases significantly the levels of il-6, il-10, il-12, tnf-a, tgf-b and inf-g(n = 3, *p<0,05, **p<0,01, vs control). Conclusions: These results suggest that HF could be recognized by Clec9a in BMDCs, inducing autophagy and promoting antigen presentation. HF-stimulated BMDCs modulate gene expression of cytokines related to the Th1, Th17 and Treg profiles, and strongly inhibit Th2 response.